Treatment of synthetic wastewater and cheese whey by the anaerobic dynamic membrane bioreactor - ÇALLI, BARIŞ; SEMERCİ, NESLİHAN (SPRINGER HEIDELBERG, 2019)
The aim of this study was to develop a laboratory-scale anaerobic dynamic membrane bioreactor (AnDMBR) for the treatment of high-strength synthetic and real cheese whey wastewater. We determined the appropriate pore size for a convenient type of support material (nylon mesh) to optimize cake layer formation. The performance of the AnDMBRs was measured in terms of chemical oxygen demand (COD) and solids removal efficiencies. During high-strength synthetic wastewater treatment, the 70-mu m pore size AnDMBR achieved COD removal efficiencies of 78% and 96% with COD loading rates of 4.03 and 2.34 kg m(-3) day(-1), respectively, while the 10-mu m pore size AnDMBR achieved 66% and 92% COD removal efficiencies at COD loading rates of 5.02 and 3.16 kg m(-3) day(-1). The 10 mu m pore size AnDMBR was operated in two periods: first period and second period (before and after physical cleaning) during high-strength synthetic wastewater treatment. The 10-mu m pore size AnDMBR removed 83% and 88% of suspended solids during period 1 and period 2, respectively. Furthermore, using a pore size of 10 mu m retained 72% of solids (973 mg L-1) in the reactor outlet. The 10-mu m pore size AnDMBR performed better than the 70-mu m pore size AnDMBR in terms of cake layer formation. The 10-mu m pore size AnDMBR was used to treat real cheese whey wastewater, resulting in COD removal efficiencies ranging from 59% (4.32 kg m(-3) day(-1)) to 97% (5.22 kg m(-3) day(-1)). In addition, 85% of suspended solids were removed from real cheese whey wastewater after treatment. The results show that dynamic membrane technology using a pore size of 10 mu m can be used to treat real industrial wastewater.
Keywords: Nylon mesh; Upflow anaerobic sludge blanket (UASB); Treatment performance; Membrane flux; Cake layer formation; Real industrial wastewater; SLUDGE BLANKET REACTOR; MESH FILTER; DIGESTION; FILTRATION; PERFORMANCE; UASB; OPERATION; ANDMBR; FLUX; BIOMETHANATION